Durability of magnesium silicate hydrate (M-S-H) MgO - SiO2 based concrete - Teo, Wen Wei (2018)
An experimental investigation is aimed at accessing and analysing the effect of different environments on the mechanical properties and durability of reactive Magnesium Oxide (MgO) based concrete, against Ordinary Portland Cement (OPC) concrete. A total of six different durability environments were applied to identical mix design of both concrete that had previously been subjected to 28 days of curing. This will form part of an investigation into the optimization of durability for the development of MgO-SiO2 based concrete. Cementitious systems based on reactive MgO (also known as Magnesia) and Micro Silica (MS), and OPC were investigated. Up to 60% of MgO was used, and to the blend, 40% of MS were incorporated as replacements for 40% of binder in OPC. Results of compressive strength, durability with regards to carbonation of concrete and other chemical attacks are reported for the estimation and evaluation of the mechanical properties of each system subjected to the different environments. A water–binder (w-b) ratio of 0.4 was used for the main group of mixes. Sodium hexametaphosphate (SHMP) was also included as a superplastizer for the MgO-SiO2-H2O system. This paper presents the results of durability characteristic properties of MgO-SiO2 based and OPC concrete of a 0.4 w-b ratio. Data from compressive strength and pH test were used to measure the mechanical properties, whereas X-ray Powder Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Thermogravimetric Analysis (TGA) were adopted to measure microstructure evaluation under the differing curing conditions. In this paper, MgO-SiO2 based samples achieved 28-day strengths of 65MPa, which was comparable to that of the P samples. The results of the experimental study identify the cementitious potential of the system, suggesting that MgO-SiO2 based concrete was not as highly affected as OPC concrete under some of the tested durability environments.